REDUCTION DEGREE OF LOW-DENSITY LIPOPROTEINS CHOLESTEROL LEVELS ACCORDING TO DIFFERENT DOSES OF STATINS; ITS EFFECT ON THE RISK OF ISCHEMIC HEART DISEASE ACUTE EPISODES DEPENDING ON TREATMENT DURATION; AND RISK OF ISCHEMIC AND THROMBOEMBOLIC STROKE. COMMENT ON THE PAPER OF LAW M.R., WALD N.J., RUDNICKA A.R. QUANTIFYING EFFECT OF STATINS ON LOW DENSITY LIPOPROTEIN CHOLESTEROL, ISCHAEMIC HEART DISEASE, AND STROKE: SYSTEMATIC REVIEW AND META-ANALYSIS. BMJ 2003; 326:1423-1427 - N. V. Perova (Рациональная фармакотерапия в кардиологии, 2016)
Comparative dose-dependent ability of different statins to lower serum low-density lipoproteins (LDL) cholesterol was determined in three large meta-analysis. Besides, it was found that standardized decrease in LDL cholesterol levels on 1.0 or 1.8 mmol/l leads to rate reduction in ischemic heart disease acute episodes as well as stroke depending on treatment duration. Effect of LDL cholesterol reduction on stroke occurrence was more significant in studies, which included a major share of patients with vascular disease, because these patients have a higher risk of thromboembolic stroke (rather than haemorrhagic stroke) in comparison with the general population.